The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/famp.12225
|View full text |Cite
|
Sign up to set email alerts
|

Parents Plus Systemic, Solution‐Focused Parent Training Programs: Description, Review of the Evidence Base, and Meta‐Analysis

Abstract: Parents Plus (PP) programs are systemic, solution-focused, group-based interventions. They are designed for delivery in clinical and community settings as treatment programs for families with child-focused problems, such as behavioral difficulties, disruptive behavior disorders, and emotional disorders in young people with and without developmental disabilities. PP programs have been developed for families of preschoolers, preadolescent children, and teenagers, as well as for separated or divorced families. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Basic descriptive statistics were often stated only partially. Although parental and child gender were not declared in all meta-analyses, one can act on the assumption that the majority of data was provided by mothers reporting on their sons (e.g., [ 40 , 50 , 56 ]). In most instances studies solely included parents of children under the age of 13 (range 0–18 years), only eight studies included youth older than 13 to some extent (e.g., [ 39 , 56 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Basic descriptive statistics were often stated only partially. Although parental and child gender were not declared in all meta-analyses, one can act on the assumption that the majority of data was provided by mothers reporting on their sons (e.g., [ 40 , 50 , 56 ]). In most instances studies solely included parents of children under the age of 13 (range 0–18 years), only eight studies included youth older than 13 to some extent (e.g., [ 39 , 56 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Although health care professionals often consider parents to be an important part of a child's mental health‐care (Barrett, Duffy, Dadds, & Rapee, ; Brendel & Maynard, ), they are often under‐utilized in the delivery of evidence‐based treatment models (Dietz, Weinberg, Brent, & Mufson, ; Taboas, McKay, Whiteside, & Storch, ; West et al., ), or involved only as adjuncts to the primary clinical work with the child (Burke & Loeber, ). However, in line with the growing body of research that supports the effectiveness of parent‐based interventions (Carr, Hartnett, Sharry, & Brosnan, ; Henggeler & Sheidow, ; Kaslow, Broth, Smith, & Collins, ), EFFT is a treatment model that increases parent involvement while also targeting the barriers to a parent's ability to support their child's recovery, regardless of age.…”
Section: A Family‐oriented and Emotion Focused Approachmentioning
confidence: 99%
“…Such support can be provided through group or individual family‐based services. Family‐based counseling or therapy is widespread and supported by solid evidence (Austin, Macgowan & & Wagner, ; Baldwin, Christian, Berkeljon & Shadish, ; Carr, Hartnett, Brosnan & Sharry, ; Pol, Hoeve, Noom et al ., ; Sexton & Alexander, ; Smith & Cook‐Cottone, ) and growing research on the efficacy and effectiveness of parental support programs supports their value (Altafim & Linhares, ; Chu et al ., ; Dretzke, Davenport, Frew et al ., ; Eyberg, Nelson & Boggs, ; Furlong et al ., ). However, much of the research on family‐based interventions or parenting programs has involved indicated or selective approaches to prevention (Baldwin et al ., ; Carr et al ., ; Chu et al ., ; Furlong et al ., ), and most parent training programs were originally developed with parents of younger children in mind (Eyberg et al ., ; Kumpfer, Whiteside, Greene & Allen, ; Ralph, Winston Tournbourou, Grigg, Mulcahy, Carr‐Gregg & Sanders, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family‐based counseling or therapy is widespread and supported by solid evidence (Austin, Macgowan & & Wagner, ; Baldwin, Christian, Berkeljon & Shadish, ; Carr, Hartnett, Brosnan & Sharry, ; Pol, Hoeve, Noom et al ., ; Sexton & Alexander, ; Smith & Cook‐Cottone, ) and growing research on the efficacy and effectiveness of parental support programs supports their value (Altafim & Linhares, ; Chu et al ., ; Dretzke, Davenport, Frew et al ., ; Eyberg, Nelson & Boggs, ; Furlong et al ., ). However, much of the research on family‐based interventions or parenting programs has involved indicated or selective approaches to prevention (Baldwin et al ., ; Carr et al ., ; Chu et al ., ; Furlong et al ., ), and most parent training programs were originally developed with parents of younger children in mind (Eyberg et al ., ; Kumpfer, Whiteside, Greene & Allen, ; Ralph, Winston Tournbourou, Grigg, Mulcahy, Carr‐Gregg & Sanders, ). There is a gap in research into interventions offered universally to parents of adolescents (Chu et al ., ; Eyberg et al ., ; Furlong et al ., ), but some such studies have shown positive effects such as improved parenting confidence (Chu et al ., ), communication (Leijten, Raaijmakers, De Castro & Matthys, ), parental satisfaction (Rickard, Brosnan, O'Laoide et al ., ) and reduced dysfunctional disciplining behavior (Leijten et al ., ), adolescent problem behavior (Chu et al ., ), and adolescent emotional difficulties (Rickard et al ., ).…”
Section: Introductionmentioning
confidence: 99%